Celostno načrtovanje javnega potniškega prometa v Ljubljanski urbani regiji - Bole, David (Georitem, 2012)
This volume discusses various aspects of planning public transport in the Ljubljana Urban Region, in which it highlights the cooperation between Ljubljana as a metropolis and its functionally connected countryside. After studying the basic social processes that guide development in this region, such as centralization and suburbanization, it focuses on traffic and public transport in this region. It analyzes the traffic flows, road use, and commuting, and dedicates special attention to commuting times. Suitable measures and best-practice examples are presented for the cases of unsustainable mobility that were indentified, especially with regard to improving spatial and temporal accessibility and transfer points in the public transport network. Proposals for integrating spatial and transport planning were developed, and ideas about drafting the development of public passenger transport in the selected corridor in the Ljubljana Urban Region were presented.